(untitled) (Cardiovascular Journal, 2016)
Background: The ostial left anterior descending coronary artery (LAD) lesion is an important target for coronary revascularization because its location subtends a large territory of myocardium. Ostial lesions have a reputation of being fibrotic, calcified, and relatively rigid. Greater degraees of rigidity and recoil resulted in lower acute gain and higher rates of target lesion revascularization (TLR) following percutaneous coronary intervention (PCI). In addition, procedural complications such as dissections, vessel closure and myocardial infarction were more frequent. Aim of the study was to evaluate a simple but innovative technique to deal with significant LAD ostial lesion. Methods: This prospective study was conducted between January 2010 and February 2013. Patients with significant angiographic de novo ostial LAD artery stenoses were identified and screened for study eligibility. An ostial stenosis was defined as an angiographic narrowing of e 70% located within 3 mm of the vessel origin. Study included all consecutive patients with ostial lesions who underwent elective PCI and stent deployment. The study population consisted of 36 patients. Results: Among 36 patients 27 (75%) were male. mean age was 55.75 ± 8.07 years. 21 (58.3%) had diabetes, 15 (41.7%) hypertension, 21 (58.3%) hypercholesterolemia, 24 (66.66%) were smoker and 18 (50%) had F/H of CAD. Among them 6 (16.7%) had STEMI, 9 (25%) had NSTEMI, 12 (33.3%) had UA and 9 (25%) CSA. CAG showed 15 (41.7%) SVD, 15 (41.7%) DVD and 6 (16.7%) were TVD. LAD ostial stenosis were 83.16 ± 10.14%. Considering procedural characteristics, DES were 33 (91.7%) and BMS were 3 (8.3%). DES polymers were Evarolimus 15 (41.7%), Zotarolimus 12 (33.3%) and Biolimus 6 (16.7%). Mean stent length were 21.75 ± 8.07 mm. Mean stent diameter were 2.83 ± 0.28 mm. Minimum follow up time was 9 months and maximum follow up time was 44 months. There were no MACE but Angina (CCS II) were 2 (5.55%) and LVF (NYHA II) were 1(2.77%). Conclusion: Precise placement of LAD ostial stent is always challenging. Several technique applied but results not always satisfactory. Our strategies were precise location of stent implantation at ostium by adopting special technique of simultaneous balloon placement from distal LM to proximal LCX preventing unwanted stent movement during its placement and also properly guiding us for precise stent placement at the ostium. Parked balloon from distal LM to LCX will also be helpful for quick measure for any plaque shifting into LCX. Cardiovasc. j. 2016; 9(1): 49-54